Influye la condición física en los indicadores de rendimiento técnico-táctico en un equipo profesional de baloncesto femenino? - Mancha-Triguero, D.; Reina, M.; García-Rubio, J.; Ibáñez, S. J. (Revista Internacional de Ciencias del Deporte, 2021)
The final result of a competition is conditioned by different factors (e.g., age, experience, competitive level) that affect the athlete`s performance. This performance may changes throughout the season depending on different variables related to training. The objectives of this research were to know the physical performance profiles of the players in different physical fitness tests grouped by their game position and to analyse the relationships between the results of the physical tests and the technical-tactical performance indicators obtained in competition. To do this, an elite female team was analysed and performed a centripetal force test, an anaerobic capacity test and two lower body strength tests. The results have shown that in women`s basketball the players have physical fitness profiles adapted to the demands of the game. In addition, Technical-tactical performance in women`s basketball is related to the physical fitness profile of the players. The 2-Point Shots Annotated (p=0.35) negatively correlated with the Explosive Distance of the anaerobic test. The 3-Point Shots Annotated correlate with the Explosive Distance of the anaerobic test (p=.007) and the Right Arch test (p=.015). Total Rebounds correlate with the Explosive Distance of the anaerobic test (p=.001) and MultiJump test Impulse (p=.036) and the Free Throws Scored with Time of the Left Arch test (p=.023). Therefore, the physical level obtained by the players in the physical fitness tests affects both the performance indicators and the final result of the competition that they obtain individually.